Study of calcium-containing compounds as catalysts for the esterification of glycerol with higher carboxylic acids - Yu. L. Zotov; D. M. Zapravdina; E. V. Shishkin; Yu. V. Popov (Тонкие химические технологии, 2023)
Objectives. To investigate the catalytic activity of calcium-containing basic catalysts for the esterification of glycerol with higher carboxylic acids in order to develop a low-waste technology for the production of multifunctional additives, as well as to assess the possibility of using the reaction products for the processing of polyvinyl chloride.Methods. The consumption of oleic acid during synthesis was monitored using a titrimetric method of analysis with visual indication. The structure of the synthesized calcium-containing catalysts was confirmed by infrared spectroscopy; elemental analysis was additionally performed for calcium glyceroxide. Quantitative and qualitative analyses of the resulting mixtures of oleic acid glycerides were carried out using chromato-mass spectrometry. A sample of a multifunctional additive was tested in a model formulation of a medical plastic compound based on polyvinyl chloride.Results. It is shown that the catalytic activity of calcium derivatives in the reaction of esterification of glycerol with higher carboxylic acids increases in the series СаО < Са(ОН)2 < Ca(C17H33COO)2 < Ca(C2H5O)2 < Ca(C4H9O)2 < Ca(C3H7O3)2, while the use of calcium glyceroxide as a catalyst in an amount from 1 to 6 mol % increases the conversion of carboxylic acid from 58 to 86% in 10 h of synthesis. However, varying the amount of calcium glyceroxide from 1.5 to 6 mol % results in no observed changes in the conversion of carboxylic acid. The multifunctional additive obtained by selecting calcium glyceroxide as a catalyst has a thermally stabilizing and plasticizing effect on the polymer composition. The introduction of the developed additive into the formulation of a polyvinyl chloride composition for medical purposes reduces the processing torque and time to reach the dry point. By combining these factors, energy costs during production were reduced by more than 11% compared to the control composition.Conclusions. It is established that calcium alcoholates catalyze the reaction of esterification of glycerol with oleic (or higher) acid to increase the conversion of the initial substances and selectivity for the formation of monoglycerides as compared with calcium oxide, hydroxide, and oleate. By optimizing the ratio of glycerol : oleic acid : calcium glyceroxide at 1 : 1 : 0.015, the maximum conversion of oleic acid of up to 86% in 10 h was obtained via synthesis. The proposed method for esterification of glycerol with higher carboxylic acids in the presence of a calcium-containing catalyst avoids the stage of purification from the catalyst to obtain a composition with multifunctional additive properties for the processing of polyvinyl chloride.